Participation in export markets and the role of R&D: establishment-level evidence from the UK Community Innovation Survey 2005 - Harris, Richard; Li, Qian Cher (Taylor & Frances, 2010)
There is a strong expectation in the literature that exporting and innovation activities (particularly R&D) are strongly related, and that the need to be innovative is increasing over time due to globalization. In this study, we find that R&D is endogenous in a model that determines which British establishments enter export markets, and when such simultaneity is taken into account the strength of the export–innovation relationship is generally quite weak (especially in the nonmanufacturing sector). Rather, we find that the size of establishments and firms, foreign ownership, the extent of international co-operation and, most importantly, the industry sector to which the establishment belongs, are the most significant in explaining which establishments are able to overcome entry barriers into overseas markets.